2017
DOI: 10.1016/j.jhlste.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Redressing the balance: Inverted hierarchies in the tourism classroom

Abstract: The research evaluates a collaborative case study to co-create the curriculum for a tourism undergraduate module. In three course design team (CDT) meetings, students selected and discussed topics and learning styles. Qualitative analysis revealed that the students involved strove to be independent learners. They favoured active learning styles and 'non-vocational' aspects of tourism. However, university bureaucracy represents a block in the design process. The paper concludes by advocating a more equal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For instance, in a survey consisting 120 tutees and 7 tutors, the tutees' average ratings were 6.97 ± 1.93 (from 1=unsatisfactory to 10=excellent). Furthermore, in an action research involving 2 lecturers and varying number of students at each and every interval (2 or 3 or 4), flipped students were seen enjoying the active learning component of the flipped classroom model (Pappalepore & Farrell, 2017). In a questionnaire survey by Hao (2016) with 84 undergraduates studying Information Technology and Education (79.1% females and 20.9% males), 60% of the students reported that they preferred the flipped instructional pedagogy than the traditional lecture method.…”
Section: Students' Preference and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a survey consisting 120 tutees and 7 tutors, the tutees' average ratings were 6.97 ± 1.93 (from 1=unsatisfactory to 10=excellent). Furthermore, in an action research involving 2 lecturers and varying number of students at each and every interval (2 or 3 or 4), flipped students were seen enjoying the active learning component of the flipped classroom model (Pappalepore & Farrell, 2017). In a questionnaire survey by Hao (2016) with 84 undergraduates studying Information Technology and Education (79.1% females and 20.9% males), 60% of the students reported that they preferred the flipped instructional pedagogy than the traditional lecture method.…”
Section: Students' Preference and Satisfactionmentioning
confidence: 99%
“…Peer instruction eliminates the monotonous banking of knowledge experienced in an instructor-centered learning space. Most authors reported that the flipped classroom model allowed students to watch videos at own time, own pace, pause, rewind, fast forward videos as they please (Braun, Ritter, & Vasko, 2014;Pappalepore & Farrell, 2017;Roach, 2014). However flipped students were found to study longer before attending class [Effect size (ES)=0.146, P=0.056] and less time after class [ES = -0152, p=0.047] (He et al, 2016).…”
Section: Learning Effort Time and Pacementioning
confidence: 99%